Influence of In-Situ Stress on the Energy Transmission of Blasting Stress Wave in Jointed Rock Mass - Qian Dong; XinPing Li; TingTing Liu (Shock and Vibration, 2021)
The study of influence of in-situ stress on energy transmission of blasting stress wave in jointed rock mass is the basis for improving the utilization rate and optimizing the distribution of explosive energy in underground rock mass during blasting excavation. Thus, a model test was carried out to explore the energy transmission of blasting stress wave in jointed rock mass under different in-situ stresses, and the energy transmitting coefficients of the blasting stress wave were derived. Then, the influencing factors such as the scale and distribution of in-situ stresses and the angle and number of joints were discussed, respectively. The results showed that the energy transmission of blasting stress wave in jointed rock mass was affected by both the intact rock and joints, and the energy transmitting coefficients first increased and then decreased with the rise of static load and lateral static load coefficient, indicating that the lower in-situ stress can enhance the energy transmission of stress wave in rock mass to some extent. While the in-situ stress was relatively large, the stress wave energy dissipation in intact rock was dominant. The number and angle of joints also had a remarkable impact on the energy attenuation of the stress wave; when the stress wave was vertically incident on the joints, the energy transmitting coefficient was the largest. For underground engineering, the orientation of the dominant structural plane and the in-situ stress state of rock mass should be determined firstly, and the blasting parameters can be optimized to improve the utilization of explosive energy and achieve the designed blasting effect.